Characterisation and outcome of RAC1 mutated melanoma. (April 2023) - Lodde, Georg C.; Jansen, Philipp; Herbst, Rudolf; Terheyden, Patrick; Utikal, Jochen; Pföhler, Claudia; Ulrich, Jens; Kreuter, Alexander; Mohr, Peter; Gutzmer, Ralf; Meier, Friedegund; Dippel, Edgar; et al.
Abstract: Background: Activating hot spot R29S mutations in RAC1, a small GTPase influencing several cellular processes including cell proliferation and cytoskeleton rearrangement, have been reported in up to 9% of sun-exposed melanomas. Clinical characteristics and treatment implications of RAC1 mutations in melanoma remain unclear. Methods: We investigated the largest set (n = 64) of RAC1 mutated melanoma patients reported to date, including a retrospective single institution cohort (n = 34) from the University Hospital Essen and a prospective multicentre cohort (n = 30) from the translational study Tissue Registry in Melanoma (TRIM; CA209-578), for patient and tumour characteristics as well as therapy outcomes. Results: From 3037 sequenced melanoma samples screened RAC1 mutations occurred in ∼ 2% of samples (64/3037). The most common RAC1 mutation was P29S (95%, 61/64). The majority of tumours had co-occuring MAP kinase mutations (88%, 56/64); mostly activating NRAS (47%, 30/64) mutations, followed by activating BRAF (28%, 18/64) and NF1 (25%, 16/64) mutations. RAC1 mutated melanomas were almost exclusively of cutaneous origin (84%, 54/64) or of unknown primary (MUP, 14%, 9/64). C > T alterations were the most frequent mutation type identified demonstrating a UV-signature for RAC1 mutated melanoma. Most patients with unresectable disease (39) received immune checkpoint inhibitors (ICI) (77%, 30/39). Objective response rate of first-line treatment in patients with stage III/IV disease was 21%; median overall survival was 47.8 months. Conclusions: RAC1 mutated melanomas are rare, mostly of cutaneous origin and frequently harbour concomitant MAP kinase mutations, particularly in NRAS . Patients with advanced disease benefit from systemic treatment with ICI. Highlights: RAC1 mutations occur in UV-exposed melanoma. RAC1 mutations frequently co-occur with NRAS mutations. Solitary RAC1 mutation without co-occurrence of other MAP kinase mutations is rare. Metastatic RAC1 patients benefit from immune checkpoint inhibition (ICI).